Двухэтапный проксимальный алгоритм для задачи о равновесии в пространстве Адамара - Ведель, Я.И.; Семёнов, В.В.; Чабак, Л.М. (Доповіді НАН України, 2020)
Предложен двухэтапный проксимальный алгоритм для приближенного решения задач о равновесии в пространствах Адамара. Данный алгоритм является аналогом ранее изученного двухэтапного алгоритма для
задач о равновесии в гильбертовом пространстве. Для псевдомонотонных бифункций липшицевого типа доказана теорема о слабой сходимости порожденных алгоритмом последовательностей. Запропоновано двоетапний проксимальний алгоритм для наближеного розв'язання задач про рівновагу в
просторах Адамара. Даний алгоритм є аналогом раніше дослідженого двоетапного алгоритму для задач
про рівновагу в гільбертовому просторі. Для псевдомонотонних біфункцій ліпшицевого типу доведено
теорему про слабку збіжність послідовностей, що породжені алгоритмом. We consider the equilibrium problem in Hadamard spaces, which extends and unifies several problems in optimization,
variational inequalities, fixedpoint
theory, and many other parts in nonlinear analysis. First, we give
the necessary facts about Hadamard metric spaces and consider the statements of equilibrium problems associated
with pseudomonotone
bifunctions with suitable conditions on the bifunctions in Hadamard spaces. Then,
to approximate an equilibrium point, we consider the twostage
proximal algorithm for pseudomonotone bifunctions. This algorithm is an analog of the previously studied twostage
algorithm for equilibrium problems in a Hilbert space. For Lipschitztype
pseudomonotone bifunctions, a theorem on the weak convergence of sequences generated by the algorithm is proved.